2018
DOI: 10.1292/jvms.17-0092
|View full text |Cite
|
Sign up to set email alerts
|

Epizootic of sarcoptic mange in raccoon dogs (<i>Nyctereutes procyonoides</i>) in relation to population density

Abstract: To examine outbreaks of mange in raccoon dogs (Nyctereutes procyonoides) with respect to population density, we analyzed camera trap videos, and isolated mites from raccoon dog carcasses. In a camera trapping survey, we categorized the skin condition of raccoon dogs, and used a number of independent videos to calculate the relative abundance index (RAI). The RAI of raccoon dogs with alopecia increased following an increase in the RAI of those without alopecia. Among 27 raccoon dog carcasses, 12 showed mange-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…On the other hand, such populations are more susceptible to infection, as lowered fitness, condition, and immune defense favor disease occurrence and spread. Also population density may strongly increase risk of disease transmission through close contact between mating pairs or group members (Sugiura et al 2018). Contact rate between individuals may be also accelerated by host behavior and sociality.…”
Section: Ecological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, such populations are more susceptible to infection, as lowered fitness, condition, and immune defense favor disease occurrence and spread. Also population density may strongly increase risk of disease transmission through close contact between mating pairs or group members (Sugiura et al 2018). Contact rate between individuals may be also accelerated by host behavior and sociality.…”
Section: Ecological Factorsmentioning
confidence: 99%
“…Sarcoptic mange is an example of a disease whose spread depends on host sociality and behavior. It is a highly contagious mite infection responsible for epizootic skin disease in populations of wild and domestic mammals worldwide (Arlian 1989;Pence and Ueckermann 2002;Sugiura et al 2018). Social carnivores are more susceptible to mange than solitary ones (Kołodziej-Sobocińska et al 2014b; Sugiura et al 2018) due to a high overlap of space, habitat use, and denning behavior, including the shared use of den sites (Kowalczyk et al 2008).…”
Section: Behavior and Socialitymentioning
confidence: 99%
“…On the other hand, previous studies have reported that the multiple paternity of the fox family and raccoons (Procyon lotor) is influenced by high population density [1,5,17,19]. By undertaking a camera trapping survey in this study area, the population density of the raccoon dogs in 2014 (when the mother of litter 1 was captured) was higher than the year when the other pregnant females were captured [24,25]. Thus, multiple paternity in wild raccoon dogs might be related to high population density, similar to that seen in foxes and raccoons.…”
mentioning
confidence: 70%
“…3 ). Epizootic sarcoptic mange in raccoon dogs might be related to high population densities [ 5 , 17 , 20 ]. The occurrence of sarcoptic mange was high in urbanized areas because of higher population densities [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infested raccoon dogs often become severely debilitated and die of asthenia [5]. Previous studies analyzed the effects of epizootic sarcoptic mange on the population dynamics of raccoon dogs [5,18,20]. However, the main transmission factor of epizootic sarcoptic mange in raccoon dogs is still unknown.…”
Section: Introductionmentioning
confidence: 99%